Harry Potter and the prisoner of Azkaban (Harry Potter (Illustrated series), 3, 1, 2018)
During his third year at Hogwarts School for Witchcraft and Wizardry, Harry Potter must confront the devious and dangerous wizard responsible for his parents' deaths.
Owl Post , Aunt Marge's Big Mistake , The Knight Bus , The Leaky Cauldron , The Dementor , Talons and Tea Leaves , The Boggart in the Wardrobe , Flight of the Fat Lady , Grim Defeat , The Marauder's Map , The Firebolt , The Patronus , Gryffindor Versus Ravenclaw , Snape's Grudge , The Quidditch Final , Professor Trelawney's Prediction , Cat, Rat, and Dog , Moony, Wormtail, Padfoot, and Prongs , The Servant of Lord Voldemort , The Dementor's Kiss , Hermione's Secret , Owl Post Again.

Harry Potter and the Order of the Phoenix (Harry Potter (Original series), 5, 1, 2022)
When the government of the magic world and authorities at Hogwarts School of Witchcraft and Wizardry refuse to believe in the growing threat of a freshly revived Lord Voldemort, fifteen-year-old Harry Potter finds support from his loyal friends in facing the evil wizard and other new terrors.
Dudley demented , A peck of owls , The advance guard , Number twelve, Grimmauld Place , The Order of the Phoenix , The noble and most ancient house of Black , The Ministry of magic , The hearing , The woes of Mrs. Weasley , Luna Lovegood , The sorting hat's new song , Professor Umbridge , Detention with Dolores , Percy and Padfoot , The Hogwarts high inquisitor , In the hog's head , Educational decree number twenty-four , Dumbledore's army , The lion and the serpent , Hagrid's tale , The eye of the snake , St. Mungo's hospital for magical maladies and injuries , Christmas on the closed ward , Occlumency , The Beetle at bay , Seen and unforeseen , The centaur and the sneak , Snape's worst memory , Career advice , Grawp , O.W.L.s , Out of the fire , Fight and flight , The Department of mysteries , Beyond the veil , The only one he ever feared , The lost prophecy , The second war begins.